Struktural Fungsional dalam Pengelolaan Desa Wisata Simarasok di Nagari Simarasok Kecamatan Baso Kabupaten Agam - Maharani, Syabilla; Magriasti, Lince (PUBLICNESS: Journal of Public Administration Studies, 2024)
The background to this research is the less than optimal management of the Simarasok Tourism Village. The type of research is a qualitative descriptive approach. The aim of this research is to analyze the Structural Functional approach in Management of the Simarasok Tourism Village in Nagari Simarasok, Baso District, Agam Regency. The results of the research show that: The Structural Functional Approach in Management of the Simarasok Tourism Village in Nagari Simarasok, Baso District, Agam Regency from four components, namely Adaptation, Goal attainment (Achievement of goals), Integration (Integration), and Latency (Latency or pattern maintenance) has been achieved. run by a larger social system, namely the Simarasok Tourism Village community, meaning that the Simarasok Tourism Village social system is able to fulfill its role and function. However, there are things that need to be improved in the Goal Attainment section, inadequate facilities and infrastructure, promises that are still electronic, resources that are not yet competent in the tourism sector.